Threats and New Protection Measures in Inland Navigation - Kasum, Josip; Vidan, Pero; Baljak, Krešimir (Promet - Traffic&Transportation, 2012)
The density of navigation in the world waterways is considerable, especially because it is more profitable, when compared to other forms of transport. In this paper the authors propose new measures for security protection of inland waterways and of ships and ports in inland navigation. Because of various kinds of threats in inland waterways navigation it is proposed to develop the International Ship and Port facility Security Code (ISPS) code suited to such navigation. Therefore the working title of the document is proposed as International Ship and Port Facility Security Code in Inland Waterways (ISPSIW).KEY WORDS: safety, threats, protection, inland navigation